(untitled) (Nigerian Journal of Technology, 2017)
Selected physical and mechanical properties of velvet bean (Mucuna pruriens) were studied at two moisture content levels of 13% and 20% (db). Compression strength characteristics were conducted under quasi-static compressive force at longitudinal and latitudinal (lateral) loading positions and the rupture forces, compressive strength, modulus of deformability, toughness, stiffness and force at bio-yield point determined as the mechanical properties at varying loading positions. Results indicated that volume (7.398 - 9.416 mm3), surface area (73.289 - 111.782 mm2), geometric mean diameter (9.18 - 11.68mm), and weight (0.872 - 1.055 g) of the velvet bean seed increased linearly with increase in moisture content. Also, the bulk density, specific gravity (0.118 - 0.112 g/mm3), sphericity (0.737 - 0.704) and aspect ratio (0.776 - 0.719) decreased linearly with increase in moisture content. These indicate that Velvet beans have wide size ranges and no single sample of the grains can effectively represent the other. In the case of the force-deformation characteristics, result indicates that the force and corresponding deformation to rupture of velvet bean seeds were found to vary from 525N, 5mm in longitudinal loading position to 800N, 7mm in lateral loading position at 13% moisture content and 131.25N, 3mm in longitudinal loading to 237.5N, 4.75mm in lateral loading at 20% (wb) moisture content. The bio-yield force, compressive strength, stiffness and toughness of the velvet bean seeds varied from 375 N, 14.412 N/mm2, 105 N/mm and 354.836 J/mm3respectively in longitudinal loading position to 475 N, 21, 961 N/mm2, 114. 286 N/mm2 and 756.961 N/mm2respectively in lateral loading position at 13% moisture content and 112.5N, 3.53N/mm2, 43.75 N/mm and 41.817 J/mm3respectively in longitudinal loading and 175 N, 6.388 N/mm2, 50 N/mm and 119.809 J/mm3respectively in lateral loading at 20% (wb) moisture content. Generally, the compressive strength of the velvet bean seeds is higher at lateral loading position than at the longitudinal loading position. http://dx.doi.org/10.4314/njt.v36i2.39